(untitled) (Journal of Economic Research & Business Administration, 2015)
В данной статье рассмотрены основные направления жилищной политики Республики Казахстан. Показан эффективный механизм государственного регулирования жилищного сектора. *** This articles describes the main areas of real estate policy of the Republic of Kazakhstan. Showa the effective mechanism of state regulation of the real estate.